CLINICAL PRESENTATION, AETIOLOGY AND COMPLICATIONS OF PANCREATITIS IN CHILDREN - Fayyaz, Zafar; Cheema, Huma Arshad; Suleman, Hassan; Hashmi, Muhammad Almas; Parkash, Arit; Waheed, Nadia (Journal of Ayub Medical College Abbottabad, 2015)
Background: Childhood Pancreatitis is an uncommon but serious condition with incidence on the rise. It manifests as acute or chronic form with epigastric pain, vomiting and elevated serum amylase and lipase. This study was conducted with the aim to determine the clinical presentation, aetiology, and complications of pancreatitis in children. Methods: This descriptive case series was conducted in the Department of Paediatric Gastroenterology, Hepatology and Nutrition, The Children’s Hospital & the Institute of Child Health, Lahore from 1st January to 31st December 2014. Seventy-two patients up to the age of 15 years having abdominal pain, Amylase >200 IU/L and/or lipase >165 IU/L, with features of acute or chronic pancreatitis on abdominal imaging; were included in study. Data analysis was done using SPSS-20. Results: Of the total 72 patients, 43 (60%) had acute pancreatitis, males were 25 (58%) and females 18 (42%) and chronic pancreatitis was diagnosed in 29 (40%), males 10 (34%) and females 19 (66%). Common clinical features were abdominal pain (100%), nausea and vomiting (79%). common aetiologies were idiopathic (40%) while choledochal cyst 8%, hyperlipidaemia 7%, biliary tract stones/sludge 7% and abdominal trauma 6%. Complications were more frequently associated with acute pancreatitis (60%) than with chronic pancreatitis (34%). Common complications were pseudopancreatic cyst (36%), ascites (17%) and pleural effusion (4%). Conclusion: Abdominal pain, nausea and vomiting were common presenting features of childhood pancreatitis. Common aetiologies were idiopathic. hyperlipidemia, biliary tract stones/sludge, choledochal cyst and abdominal trauma. Common complications were Pseudopancreatic cyst, ascites and pleural effusion.